Evaluation of the Acute Toxicity of Acetaminophen in Mice - H Hashem, Suhad; M. K. AL-Rekabi, Falah; Ali, Selman (The Iraqi Journal of Veterinary Medicine, 2023)
Acetaminophen (N-acetyl-para-aminophenol, APAP), widely used for pain relief across specie, poses significant toxicity risks. This study ‎aimed to assess the acute toxicity profile of APAP by determining the median toxic dose ‎‎(TD50) in a ‎‎murine model. Sixty male Balb/c mice, aged 8 weeks and weighing 20-30 ‎g, were randomized into six equal groups. Five groups received single oral doses of APAP (150, 200, 300, 500, and 700 mg/kg BW), while the control group received distilled water. The TD50 was ‎computed utilizing the probit method. Animals were ‎‎monitored for 24 h for ‎any sign indicative of clinical toxicity. Post-exposure, liver and kidney necropsies were conducted for histopathological analysis. Predominant symptoms of toxicity included prostration, hematuria, heightened agitation, lacrimation, cyanosis, and recumbency across doses from 150 to 700 mg/kg BW. The TD50 for APAP was estimated to be 732 ‎mg/kg BW. The liver histopathological examination of mice treated ‎‎with 700 mg/kg BW APAP ‎revealed severe multifocal hyper eosinophilic hepatocytes, indicating areas of centrilobular ‎necrosis, disorganized ‎‎hepatic cords, and multiple hemorrhage regions. The kidney ‎examination exhibited no pathological changes in treated mice with 700 mg/kg BW ‎‎APAP. In ‎conclusion this investigation provides critical insights into the acute toxicity profile of APAP. The findings not only highlight the ‎‎potential risk associated with APAP usage but also the ‎necessity of strict monitoring for stringent dosage control. Further research is also ‎‎needed to ‎understand the underlying mechanism of APAP-induced toxicity and pave the way for the ‎development of efficacious therapeutic ‎strategies to counter APAP overdose‎‎‎‎.